PEMILIHAN PASANGAN PERNIKAHAN BERDASARKAN WETON (Studi Fenomenologi Nilai Bimbingan dan Konseling Pada Tradisi Masyarakat Di Desa Sepande Sidoarjo) - CHOLIL CHOLIL; AMRIANA AMRIANA; ZORA RIZKYTA ANINDINI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2021)
The purpose of this study is to analyze the phenomenon of the practice of calculating weton which is still carried out in the village of Sepande in relation to the values ??of marriage guidance and counseling. This research uses qualitative research with descriptive analysis. This study concludes that the calculation of weton for a mate comes from the sum of the neptu days and the market for each prospective bride and groom. However, in today's society it is not as extreme as it used to be, if the weton between men and women do not have compatibility, then both of them have to separate and find another partner. The calculation of weton is only one of the considerations beyond bibit, bebet and bobot factors whether they will continue the marriage or not. Calculation of weton in the village of Sepande is not like in the past because times have changed. The values ??of marriage counseling have been included in the community tradition so that the weton calculation is considered as advice to be careful when getting married in the future.